PENERBITAN LETTER OF CREDIT SEBAGAI JAMINAN PEMBAYARAN PERDAGANGAN EXIM DALAM PERSPEKTIF SYARIAH - Miftakhul Huda (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
A letter of credit, or letter of credit, is a letter from the bank that guarantees that the buyer's payment to the seller will be received on time and in the correct amount. If the buyer cannot make payment for the purchase, the bank is obliged to cover the entire or remaining purchase amount. . Due to the nature of international transactions, including factors such as distance, different laws in each country, and the difficulty in getting to know each party personally, the use of letters of credit has become a very important aspect of international trade to protect both buyers and sellers. The aim of this research is to determine the vital function of letters of credit from a sharia perspective and to determine the consequences of default on payments, while the research method used in this research is qualitative research with a literature review approach. From this research it can be concluded that letters of credit from a sharia perspective are based on the National Sharia Council's fatwa regarding Sharia Import L/Cs, so the implementation of sharia import L/Cs can use the following contracts: Wakalah bil Ujrah, Qard, Murabahah, Salam/Istisna' , Mudarabah, Musyarakah, and Hawalah. Wakalah bil Ujrah is the granting of authority from participants to the insurance company to manage participant funds in exchange for providing ujrah (fee). A letter of credit acts as: - A letter of instruction to carry out a sale and purchase contract that has been executed - A debt letter from the issuing bank to a correspondent bank overseas - A letter of guarantee for the costs of obtaining goods and at the same time their shipment by the notification bank to the exporter.